Collecting East and West - Bracken, Susan (Susan Caroline); Gáldy, Andrea M.; Turpin, Adriana (Collecting histories., 2013)
If collecting the rare and valuable is an entirely normal trait of human behaviour, amassing objects from far-away places has also long played a role in the history of collecting. ""East"" and ""West"", or ""North"" and ""South"", for that matter, are of course entirely relative to one's particular geographical position. Therefore, it is interesting that collecting exotic objects is an endeavour that unites humanity over millennia and round the globe. The ancient Assyrians did so as assiduously as ei ...